CIVIL-MILITARY CORRIDOR RESILIENCE MODEL FOR INFRASTRUCTURE MANAGEMENT IN INDONESIA’S OUTERMOST BORDER ISLAND: EVIDENCE FROM MIANGAS ISLAND - Brantas Suharyo G; Thamrongchai Noonphakdee; Phongpincharn Suksiengsri (PT. Jurnal Center Indonesia Publisher, 2026)
Infrastructure management in outermost border islands is not only a matter of physical development, but also a strategic issue related to sovereignty, community welfare, connectivity and national defence. This article examines infrastructure management on Miangas Island, one of Indonesia’s northernmost outer islands bordering the Philippines. Although Miangas already has several basic and strategic infrastructures, including roads, an airport, a port, electricity facilities, clean water sources, telecommunications, health facilities and security infrastructure, these assets have not yet functioned as an integrated and reliable system. The main problem is therefore not the absence of infrastructure, but the gap between physical availability and functional performance. This study uses a qualitative descriptive-analytical approach based on field observation, semi-structured interviews and document review. Data were analysed using the Miles and Huberman model, supported by STEEP+M and SWOT analysis. The findings show that infrastructure management in Miangas is influenced by three main indicators: infrastructure availability and quality, connectivity and accessibility, and infrastructure sustainability. Internally, Miangas has strengths in its strategic geography, existing infrastructure assets, state institutional presence, social cohesion and strong national identity. However, these strengths are constrained by weak service quality, limited maintenance, unstable connectivity, a fragile local economy and inadequate maritime surveillance. Externally, Miangas benefits from national legal support, strategic policy status and Indonesia–Philippines cooperation, but faces threats from cross-border dependence, illegal fishing, border violations, environmental pressure and geopolitical sensitivity. The SWOT analysis places Miangas in the WO quadrant, meaning that external opportunities should first be used to overcome internal weaknesses. This article proposes the Civil-Military Corridor Resilience Model as an integrated framework that connects public services, logistics, energy, local markets, maritime security and territorial defence in one border resilience system.